Effects of a 12-Week Exercise Training Program on Physical Function in Institutionalized Frail Elderly. (11th January 2018) - Ferreira, Cristiane Batisti; Teixeira, Pâmela dos Santos; Alves dos Santos, Geiane; Dantas Maya, Athila Teles; Americano do Brasil, Paula; Souza, Vinícius Carolino; Córdova, Cláudio; Ferreira, Aparecido Pimentel; Lima, Ricardo Moreno; Nóbrega, Otávio de Toledo
Abstract : With the increase in life expectancy, the Brazilian elderly population has risen considerably. However, longevity is usually accompanied by problems such as the loss of functional capacity, cognitive decline, frailty syndrome, and deterioration in anthropometric parameters, particularly among those living in long-term care facilities. This randomized controlled trial aimed to verify the effects of exercise training on biochemical, inflammatory, and anthropometric indices and functional performance in institutionalized frail elderly. The sample consisted of 37 elderly people of both genders, aged 76.1 ± 7.7 years, who were randomly allocated into 2 groups: 13 individuals in the exercise group (EG) and 24 in the control group (CG). Anthropometrics, clinical history, functional tests, and biochemical evaluation were measured before and after the completion of a physical exercise program, which lasted for 12 weeks. The 12-week exercise program for frail elderly residents in a long-term care facility was efficient in improving muscle strength, speed, agility, and biochemical variables, with reversal of the frailty condition in a considerable number. However, no effects in anthropometric and inflammatory parameters were noted.